2001
DOI: 10.1074/jbc.m106950200
|View full text |Cite
|
Sign up to set email alerts
|

A Secreted Aminopeptidase of Pseudomonas aeruginosa

Abstract: Using leucine-p-nitroanilide (Leu-pNA) as a substrate, we demonstrated aminopeptidase activity in the culture filtrates of several Pseudomonas aeruginosa strains. The aminopeptidase was partially purified by DEAE-cellulose chromatography and found to be heat stable. The apparent molecular mass of the enzyme was ϳ56 kDa; hence, it was designated AP 56 . Heating (70°C) of the partially purified aminopeptidase preparations led to the conversion of AP 56 to a ϳ28-kDa protein (AP 28 ) that retained enzyme activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 51 publications
7
70
0
1
Order By: Relevance
“…PA2939 encodes a recently characterized, secreted, zinc-dependent metalloprotease (Cahan et al, 2001). Culture supernatants derived from mutants of the las QS system (DlasR, DlasI, DlasRI) and Dvfr did not contain any of the major isoforms of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…PA2939 encodes a recently characterized, secreted, zinc-dependent metalloprotease (Cahan et al, 2001). Culture supernatants derived from mutants of the las QS system (DlasR, DlasI, DlasRI) and Dvfr did not contain any of the major isoforms of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions at the C Terminus Resulting in Active rLAP-Cahan et al (17) reported the existence of a processed form of PA-LAP beginning at Gly-39. We, therefore, attempted to recapitulate this protein via expression of a construct we termed rLAP53 (all wild type amino acids from 40 to 536 were included, with an initiating methionine in place of Gly-39; see Fig.…”
Section: N-terminal Sequence and Mass Spectrometry Analysis Of Rlap55-mentioning
confidence: 99%
“…ing protease, we generated active site mutants and re-assessed processing at the N terminus. PA-LAP is a zinc-dependent enzyme and exhibits high sequence homology in its activity domain to LAP from Streptomyces griseus (17). Sequence alignments of PA-LAP with the Streptomyces enzyme and other LAPs suggested that zinc ions coordinated at the active site likely involve the side chains of the amino acids His-296, Asp-308, Glu-341, Asp-369, and His-467 (17).…”
Section: Table 2 Specific Activity Of Protease-treated Rlap Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly abundant band in untreated fraction 1, near 50 kDa, was identified as the aminopeptidase PepB (PaAP) (40), which is greatly diminished in the same fraction of the vesicles from EBHtreated cells. OprF, the next protein identified, at ϳ37 kDa, is much more apparent in both of the EBH fractions than in the untreated fractions, verifying the Western blot data described above.…”
Section: Epoxides Affect Cif Packaging In a Cifr-independent Fashionmentioning
confidence: 99%